2011
DOI: 10.1007/s00232-011-9369-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts and Cytoskeletal Proteins in Placental Microvilli Membranes from Preeclamptic and IUGR Pregnancies

Abstract: Intrauterine growth restriction (IUGR) and preeclampsia (PE) are leading causes of perinatal and maternal morbidity and mortality. Previously we reported the expression of lipid rafts in classical microvillous membrane (MVM) and light microvillous membrane (LMVM), two subdomains in apical membrane from the human placental syncytiotrophoblast (hSTB), which constitute the epithelium responsible for maternal-fetal transport. Here the aim was to study the raft and cytoskeletal proteins from PE and IUGR. Microdomai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…Channels in Domains and Subdomains from Placental hSTB Apical (MVM, LMVM) and basal membranes (BM) from NP and from PE and IUGR placentas were isolated and purified using the protocol described in ''Materials and Methods'' section. We found similar enrichment markers and cross-membrane contamination markers as described fully in previous work (Jimenez et al 2004;Riquelme et al 2011). We purified the membranes from 11 NPs, 4 PE placentas, and 5 IUGR placentas.…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…Channels in Domains and Subdomains from Placental hSTB Apical (MVM, LMVM) and basal membranes (BM) from NP and from PE and IUGR placentas were isolated and purified using the protocol described in ''Materials and Methods'' section. We found similar enrichment markers and cross-membrane contamination markers as described fully in previous work (Jimenez et al 2004;Riquelme et al 2011). We purified the membranes from 11 NPs, 4 PE placentas, and 5 IUGR placentas.…”
Section: Resultssupporting
confidence: 60%
“…However, there was a difference between MVM and LMVM, which are the two subdomains from apical membranes, in that K v 2.1 expression was 26 ± 8% in the LMVM and 59 ± 9% in the MVM. In previous reports (see brief review in Riquelme 2011), we suggested that the two subdomains from the apical hSTB membranes were correlated: MVM corresponded to the microvillous finger-like region of the apical subdomain, and LMVM corresponded to the apical subdomain that constituted the base of the finger-like projections (Godoy and Riquelme 2008;Riquelme et al 2011;Riquelme 2011). Then, we determined that most of the K v was located in the microvillous finger-like region.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations